The Benefits of Ultrasound, Eccentric Exercise, and Neuromuscular Taping in Reducing Elbow Pain Caused by Tennis Elbow - Rahma Septiara; Isnaini Herawati (International Journal of Science and Society, 2023)
Tennis elbow, commonly known as lateral epicondylitis, is a problem in the tendons around the elbow, which act as a driving force for the extensor muscles of the hand. Apart from tennis players, this case also often occurs in workers who use heavy equipment or perform repetitive and excessive gripping tasks, lifting, or circular arms movements. Tennis elbow is a prevalent thing for patients who seek medical help because of pain in the elbow. Tennis elbow is caused by muscle contractions in the elbow joint that occur repeatedly in sports activities such as playing badminton, doing daily activities, or other work, which gives repeated loads to the forearm muscles resulting in the appearance of pain on the outside of the elbow. This case study aims to discover the benefits of providing physiotherapy interventions in the form of Ultrasound (US), Eccentric Exercise, and Neuromuscular Taping in conditions of elbow pain due to tennis elbow. The research method used is a case study. The respondent in the study was a 23-year-old patient who was a badminton player at the Badminton UKM Muhammadiyah University of Surakarta. This research was conducted six times for two weeks. Patients were evaluated using the Visual Analogue Scale (VAS). The results of physiotherapy intervention in the form of Ultrasound (US), Eccentric Exercise and Neuromuscular Taping showed a decrease in tenderness in the lateral epicondyle of the right elbow joint from 7 VAS to 3 VAS and movement pain from 7 VAS to 2 VAS. In conclusion, by providing physiotherapeutic interventions in the form of Ultrasound (US), Eccentric Exercise, and Neuromuscular Taping, there are benefits in reducing pain on the outside of the elbow against the condition of the tennis elbow.